2023
DOI: 10.1142/s0129065723500466
|View full text |Cite
|
Sign up to set email alerts
|

A Class-Imbalance Aware and Explainable Spatio-Temporal Graph Attention Network for Neonatal Seizure Detection

Abstract: Seizures are the most prevalent clinical indication of neurological disorders in neonates. In this study, a class-imbalance aware and explainable deep learning approach based on Convolutional Neural Networks (CNNs) and Graph Attention Networks (GATs) is proposed for the accurate automated detection of neonatal seizures. The proposed model integrates the temporal information of EEG signals with the spatial information on the EEG channels through the graph representation of the multi-channel EEG segments. One-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…While such methods have shown promising results, physiological research has shown that the functional connectivity of the brain is not solely related to distance [16], and thus, defining an appropriate graph structure of EEG signals remains an open problem.Moreover, constructing the graph structure manually may not be the best option since each individual's brain functional connectivity has its specificity, making it challenging to generalize a general graph structure across different individuals [23][24][25]. Recently, Chen et al [26] proposed a soft connection graph learning model leveraging a self-attention mechanism for depression detection tasks, which results in a more precise and concise representation of the EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…While such methods have shown promising results, physiological research has shown that the functional connectivity of the brain is not solely related to distance [16], and thus, defining an appropriate graph structure of EEG signals remains an open problem.Moreover, constructing the graph structure manually may not be the best option since each individual's brain functional connectivity has its specificity, making it challenging to generalize a general graph structure across different individuals [23][24][25]. Recently, Chen et al [26] proposed a soft connection graph learning model leveraging a self-attention mechanism for depression detection tasks, which results in a more precise and concise representation of the EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Just like in other fields [20][21][22][23][24][25][26][27][28], weather forecasting systems driven by spatio-temporal data and based on deep learning (DL) [29][30][31][32][33][34][35][36][37] have demonstrated superior performance compared to Numerical Weather Prediction (NWP) methods [38][39][40][41][42]. Nevertheless, these global weather forecasting models face challenges in balancing the trade-off between forecasting coverage and computational efficiency.…”
Section: Introductionmentioning
confidence: 99%